Materials for the biography of metropolitan Parthenius of Laodicea (? — 1704) - Nadezhda Chesnokova (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
Parthenius, Metropolitan of Laodicea, more often called Parthenius Neboza in Russian historiography, is known as the author of one of the translations into Russian of the post-Byzantine Prediction about Constantinople, as well as a panegyric in honour of the capture of Azov by the troops of Tsar Peter I and his own autobiography in Russian. The texts of Parthenius have long been familiar to researchers. It is generally accepted that Parthenius was a Russian or a native of Ukraine, a traveler in the Orthodox East. During his travels, he helped the Russians taken prisoner, ransomed them to freedom, and performed worship in the Slavic language. Other evidence about the metropolitan, except for what he told about himself, is practically non-existent in scholarly literature. Based on archival documents, the author of this article demonstrates that Parthenius was a Greek by birth, the evidence of the metropolitan’s autobiography is correct, while his consecration to Russian metropolitan sees as well as the origin of the Russian texts of Parthenius require further study. The appendix publishes the autobiography of the Metropolitan.